5x-(4*-3x+5)=-3

Simple and best practice solution for 5x-(4*-3x+5)=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(4*-3x+5)=-3 equation:


Simplifying
5x + -1(4 * -3x + 5) = -3

Multiply 4 * -3
5x + -1(-12x + 5) = -3

Reorder the terms:
5x + -1(5 + -12x) = -3
5x + (5 * -1 + -12x * -1) = -3
5x + (-5 + 12x) = -3

Reorder the terms:
-5 + 5x + 12x = -3

Combine like terms: 5x + 12x = 17x
-5 + 17x = -3

Solving
-5 + 17x = -3

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5' to each side of the equation.
-5 + 5 + 17x = -3 + 5

Combine like terms: -5 + 5 = 0
0 + 17x = -3 + 5
17x = -3 + 5

Combine like terms: -3 + 5 = 2
17x = 2

Divide each side by '17'.
x = 0.1176470588

Simplifying
x = 0.1176470588

See similar equations:

| (x^2)/1.66-x=0.497 | | (x^2)/1.66-x=0 | | -2x-3*6x-11=-7 | | 259=-6x+19 | | 5m-9=26 | | -18-6e=6(1+3e) | | (7/3b)3 | | 6/a=4/3 | | 5x-2x^2+3x+4x^2= | | -6x+9+7x=15-31 | | -6(1+5m)=54 | | 5000/.84 | | 5000*/0.84 | | 84=12*(X) | | 5x+2x^2+3x-4x^2= | | 7x-2*2=10 | | 5x+2x^3-9x-8x^3= | | -6(1+5l)=54 | | 4x^2+6x=y-2 | | 3p-5=(p-1)(p-2) | | (x+4)(x+4)-14=0 | | 7x/35=4x-5/6 | | 2x^2+85-10=0 | | 2x+2=35 | | 4a+(-7a)= | | 18=3(3e-6) | | x^2-500*x+1000=0 | | 1/5x5/6 | | x^3-7x^2+14x-3=0 | | 9y+2y-3y= | | z+9=y+12 | | -5(2t+7)=-15 |

Equations solver categories